Infant Weight and Mother's Age with Perineal Rupter - Suwardi, Suyanti; Panjaitan, Ivan sri marsaulina; Harahap, Novy Ramini (Poltekkes Kemenkes Riau Under Health Ministry Republik Indonesia, 2022)
Based on data from the World Health Organization (WHO) for 2020, it is explained that around 800 women die from complications of pregnancy or childbirth worldwide every day. The maternal mortality ratio in developing countries is 240/100 000 births and 16/100 000 in developed countries. The risk factors for maternal death are bleeding, infection and pre-eclampsia. To find out the relationship between infant weight and mother's age with Perineal Rupture at the Pratama Niar Clinic Medan in 2021. Design This study used an analytic survey with a cross-sectional approach, where data was taken using secondary data, the samples taken in this study were 53 people, with using a total population of 111 people. Processing techniques using the chi-square test. The data obtained from the results of statistical tests showed that there was a relationship between infant weight and perineal rupture with p = 0.029 (p = 0.03) and there was a relationship between maternal age and perineal rupture p = 0.010 (p = 0.01) in the clinic. Pratama Niar Medan in 2021. There is a relationship between baby's weight and mother's age with perineal rupture at the Pratama Niar Medan Clinic in 2021